Electronic medical record systems data use in decision-making and associated factors among health managers at public primary health facilities, Dodoma region: a cross-sectional analytical study - Kessy, Eusebi Cornelius; Kibusi, Stephen Mathew; Ntwenya, Julius Edward (Frontiers in Digital Health, 2024)
Background Tanzania has shown some improvements in the adoption of electronic medical record (EMR) systems in public health facilities; however, the rate of utilization of data generated from EMRs among health managers is not well documented. This study aims to assess the use of electronic medical record systems data in decision-making among health managers at public primary health facilities in Dodoma Region, Central Tanzania. Methods A facility-based quantitative cross-sectional analytical study was conducted among 308 randomly selected health managers. A self-administered questionnaire supplemented with documentary review was used. Descriptive summary statistics and bivariable and multivariable logistic regression analyses (crude and adjusted odds ratios) were used. A P-value of <0.05 was used to declare statistically significant associations. Results Overall, more than a third (40.6%) of the health managers, that is 174 of the 308 included in the study, reported using data generated by EMR systems in decision-making. One-third (33.4%) of the health managers were adequately using data generated by EMR systems, of which 39.3% used data to support continuous quality improvement initiatives. Among the facilities visited, only nine (30%) had good documented EMR systems data use. Access to computers [adjusted odds ratio (AOR) = 4.72, 95% confidence interval (CI): 1.65, 13.48, p-value (p) = 0.004] and discussions on EMRs during meetings (AOR = 2.77, 95% CI: 1.01, 7.58, p = 0.047) were independent predictors of EMR system data use. Those who reported having EMR systems in all working areas were seven times more likely to use EMR system data (AOR = 7.23, 95% CI: 3.15, 16.59, p = 0.001). The respondents with good perceived EMR system information quality were more likely to use EMR system data (AOR = 2.84, 95% CI: 1.50, 5.39, p = 0.001) than those with poor perception. Furthermore, health managers who had excellent knowledge of computers and data use had higher odds of using EMR system data (AOR = 1.84, 95% CI: 3.38, 10.13, p = 0.001) compared with their counterparts. Conclusions The findings of this study indicate that utilization of EMR system data in decision-making among health managers was optimal. It was found that training in itself is insufficient to improve use of EMR, which points to more organizational aspects of work routine as a challenge. Hence, a comprehensive approach that addresses these factors is essential for maximizing EMR system data use in decision-making.